2016
DOI: 10.1017/s1466252316000189
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of proventricular dilatation disease

Abstract: Bornaviruses cause neurologic diseases in several species of birds, especially parrots, waterfowl and finches. The characteristic lesions observed in these birds include encephalitis and gross dilatation of the anterior stomach - the proventriculus. The disease is thus known as proventricular dilatation disease (PDD). PDD is characterized by extreme proventricular dilatation, blockage of the passage of digesta and consequent death by starvation. There are few clinical resemblances between this and the bornavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 155 publications
(258 reference statements)
1
24
0
Order By: Relevance
“…BoDV-1 was recently identified as the cause of human death after organ transplantation -the first hard evidence that BoDV-1 can actually infect humans and cause disease [6]. BoDV-1-infection may induce a large spectrum of neurological disorders ranging from immune-mediated acute encephalitis to non-inflammatory behavioral alterations [7,8]. Previous studies demonstrated that BoDV-1 establishes a persistent infection in the hippocampus and limbic lobe of rodents in the neonatal period, which induced cognitive deficits and mental disorders [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…BoDV-1 was recently identified as the cause of human death after organ transplantation -the first hard evidence that BoDV-1 can actually infect humans and cause disease [6]. BoDV-1-infection may induce a large spectrum of neurological disorders ranging from immune-mediated acute encephalitis to non-inflammatory behavioral alterations [7,8]. Previous studies demonstrated that BoDV-1 establishes a persistent infection in the hippocampus and limbic lobe of rodents in the neonatal period, which induced cognitive deficits and mental disorders [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the parrot B240818, the source of infection is unknown; however, we suspect that parrot bornavirus 4 (PaBV-4) entered via the olfactory pathway and migrated to brain [18], causing a lethal encephalitis; without neurological signs perceptible by the owner. The absence of clinical signs in bornavirus-infected parrots with brain lesions has previously been reported [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the parrot B240818, the source of infection is unknown; however, we suspect that parrot bornavirus 4 (PaBV-4) entered via the olfactory pathway and migrated to brain [18], causing a lethal encephalitis; without neurological signs perceptible by the owner. The absence of clinical signs in bornavirus-infected parrots with brain lesions has previously been reported [18]. Therefore, in this case, probably the virus followed one of the postulated pathways, which consist of the centrifugal spread of virus from brain, passing down the spinal cord, affecting the parasympathetic and sympathetic nerves and the organs innervated by them (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations